ANALISIS ASPEK PERPAJAKAN ATAS JASA SEWA KANTOR VIRTUAL - Dinar, Muhammad Pranasa Aranta Syaiful (Direktorat Jenderal Pajak, 2021)
This study aims to analyze the taxation aspects of virtual office rental services. With the issuance of PMK-147/PMK.03/2017, it is hoped that taxpayers will find it easier to carry out their tax obligations related to virtual office rental services. Using a descriptive study approach, this qualitative research is expected to describe and understand the phenomenon of virtual office rental services with a deep focus. The study results indicate that there are still differences in the definition of a virtual office between taxpayers and the DGT, giving rise to the practice of imposing different virtual office rental taxes between taxpayers. Income from virtual office rental services is subject to Income Tax Article 4 paragraph (2), Income Tax Article 23, and Income Tax Article 4 paragraph (1). Thus, regulatory certainty is needed on the taxation of virtual office rental services.